2013
DOI: 10.1080/01635581.2013.749292
|View full text |Cite
|
Sign up to set email alerts
|

Flavanols from Japanese Quince (Chaenomeles Japonica) Fruit Inhibit Human Prostate and Breast Cancer Cell Line Invasiveness and Cause Favorable Changes inBax/Bcl-2mRNA Ratio

Abstract: Polyphenols are natural compounds of high structural diversity which translates into a very wide spectrum of biological activities, including chemoprevention. Here we report that a Japanese quince fruit flavanol preparation (JQFFP) caused favorable changes in Bax/Bcl-2 mRNA ratio, which rendered normal and cancer cells more resistant and more sensitive, respectively, to apoptosis. DU145 human prostate cancer cells were characterized by the most advantageous Bax/Bcl-2 ratio. The growth and invasiveness of MDA-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…Migration assay. Cell migration assay was performed using the BD FalconTM 24-Multiwell Insert plate system (Becton Dickinson, Bedford, MA, USA), as described previously, with a slight modification (Lewandowska et al, 2013). Colo-205 cells were resuspended in a serumfree medium with or without PF-3845 (0-100 μM) and plated onto the upper chamber at the densities of 1 × 10 5 per 500 μL.…”
Section: Culture Conditions Human Colon Adenocarcinomamentioning
confidence: 99%
“…Migration assay. Cell migration assay was performed using the BD FalconTM 24-Multiwell Insert plate system (Becton Dickinson, Bedford, MA, USA), as described previously, with a slight modification (Lewandowska et al, 2013). Colo-205 cells were resuspended in a serumfree medium with or without PF-3845 (0-100 μM) and plated onto the upper chamber at the densities of 1 × 10 5 per 500 μL.…”
Section: Culture Conditions Human Colon Adenocarcinomamentioning
confidence: 99%
“…Invasion studies were conducted using the Matrigel BM matrix assay, developed for the measurement of tumor cell invasiveness, as described previously (18). We used BioCoat Matrigel Downloaded by [McMaster University] at 07: 30 22 December 2014 invasion chambers [24-well cell culture inserts containing an 8.0-μm PET membrane with a uniform layer of Matrigel (Becton Dickinson, Bedford, MA)].…”
Section: Invasion Assaymentioning
confidence: 99%
“…Because of its anti-inflammatory, antibacterial, antioxidant and immunoregulatory properties Chaenomeles japonica plant has been widely used in traditional Chinese medicine. Recently it was also identified as cancer chemopreventive agent with proliferation, invasiveness and angiogenesis inhibition effect (Lewandowska et al 2013;Gorlach et al, 2011). Moreover, our previous results identified Japanese quince polyphenols as potent inhibitors of carbohydrates digestive enzymes (Zakłos-Szyda et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, we found that it inhibits protein tyrosine phosphatase 1B (PTP1B), known as the major negative regulator in insulin and leptin signaling. Taking into account that these fruits are a rich source of polyphenolic compounds (mainly catechins and procyanidin oligomers) possessing numerous biological activities (Strugała et al, 2016;Tarko et al, 2014;Bahadoran et al, 2013;Lewandowska et al, 2013;Gorlach et al, 2011;Stręk et al, 2007), we hypothesized that JQ extract can also activate AMPK. Recent reports evidenced black soybean seed coat and grape seed procyanidins as the agents responsible for AMPK activation and glucose uptake in mice and rats (Yamashita et al, 2016;Crescenti et al, 2015;Kurimoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%